Anxiety and depression in Portuguese patients with Chronic Obstructive Pulmonary Disease: a multicentre cross-sectional study - Jácome, Cristina (2015)
Objectives: To assess symptoms of anxiety and depression among Portuguese patients with chronic obstructive pulmonary disease (COPD) and associated predictive factors. Study design: A multicentre, cross-sectional study. Setting: Three primary care centres and one district hospital in the central region of Portugal. Participants: 302 Portuguese outpatients with COPD. Methods: Symptoms of anxiety and depression were assessed with the Hospital Anxiety and Depression Scale (HADS). Scores ≥8 were considered clinically significant. Results: This sample of patients had a mean age of 67±12 years and 41% were female. COPD was graded as mild in 106 (35.1%), moderate in 106 (35.1%) and severe-to-very-severe 90 patients (29.8%). Clinically significant anxiety was found in 53.3% of patients and symptoms of depression in 45.4%. Symptoms of anxiety were associated with limitation of activities (OR 1.39, 95% CI 1.04-1.84), age (0.97, 95% CI 0.94-0.99) and female gender (OR 0.37; 95% CI 0.20-0.66). Symptoms of depression were associated with functional mobility (OR 1.91, 95% CI 1.38-2.66) and limitation of activities (OR 1.12, 95% CI 1.04-1.21). Conclusions: A high proportion of Portuguese patients with COPD experience symptoms of anxiety and depression. National pulmonary rehabilitation programmes might need to include collaborative self-management interventions to address patients’ emotional needs.